2017
DOI: 10.1186/s12917-017-1092-6
|View full text |Cite
|
Sign up to set email alerts
|

Small-sized newborn dogs skeletal development: radiologic, morphometric, and histological findings obtained from spontaneously dead animals

Abstract: BackgroundVery little is known about neonatal skeletal development in small-sized purebred dogs. In order to improve this knowledge, 27 spontaneously dead puppies belonging to small-sized breeds were enrolled in this study for radiologic, histological and morphometric investigations.ResultsThe appearance of the limb secondary ossification centers and the onset of their formation were clearly observed by x rays and confirmed by histological evidences. Radiographic and anatomic measurements of limb bones length … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 33 publications
2
12
0
1
Order By: Relevance
“…In this study, some important information about the serial changes in skeletal development of forelimb during the six months of age, in medium-sized Nigerian indigenous dogs was provided. The radiographic findings from the postnatal skeletal development of the forelimb in Nigerian indigenous dogs were similar to that reported b [17] and [18] except for the humerus, which presents the appearance of SOC at the proximal and distal epiphyses at 4week-old unlike the reported studies that appeared from 8-week-old and 3-week-old respectively. However, Von Dfeil and DeCamp [19] stated that the SOC at proximal and distal epiphyses of humerus and radius appeared at prenatal, while the SOC of the ulna, carpals, metacarpals and phalanges appeared from 3 to 4 months of age.…”
Section: Discussionsupporting
confidence: 86%
“…In this study, some important information about the serial changes in skeletal development of forelimb during the six months of age, in medium-sized Nigerian indigenous dogs was provided. The radiographic findings from the postnatal skeletal development of the forelimb in Nigerian indigenous dogs were similar to that reported b [17] and [18] except for the humerus, which presents the appearance of SOC at the proximal and distal epiphyses at 4week-old unlike the reported studies that appeared from 8-week-old and 3-week-old respectively. However, Von Dfeil and DeCamp [19] stated that the SOC at proximal and distal epiphyses of humerus and radius appeared at prenatal, while the SOC of the ulna, carpals, metacarpals and phalanges appeared from 3 to 4 months of age.…”
Section: Discussionsupporting
confidence: 86%
“…The investigation made it also possible to reliably classify 19 puppies belonging to 5 previously uncategorized breeds using the neural nets. Moreover, it suggested that canine cadavers can represent a valid alternative to in vivo animal models in the study of skeleton development, as previously demonstrated [ 36 , 46 ].…”
Section: Discussionmentioning
confidence: 82%
“…Recently, an allometric study was performed on newborn puppies belonging to small-sized breeds. The study included craniometric measures, but skull morphotype was not considered [ 36 ]. Since literature lacks study design standardization, the present investigation aimed to evaluate skull morphometry in newborn dogs and to classify puppies belonging to previously non-categorized canine breeds.…”
Section: Introductionmentioning
confidence: 99%
“…Another morphometric study was recently carried out on 27 spontaneously dead small-sized new-born dogs. Radiographic measurements of the length of long limb bones were positively correlated with the dogs' age and body weight [39]. However, since this study was carried out on dead animals, it is not possible to make any considerations about bone growth rate in relation to age or body weight.…”
Section: Discussionmentioning
confidence: 91%